Dari Ilmu Ke Tindakan: Literasi Keuangan, Pengetahuan, Dan Kontrol Diri Dalam Pengelolaan Finansial Mahasiswa - Robby Alexander Chandra; Ickhsanto Wahyudi (Universitas 45 Surabaya, 2025)
Intelligence in dealing with life is obtained through education, parenting, and experience. Students need to understandfinancial manajement which is influenced byfinancial literacy